Algebraic specification of information systems - Karimaa, Erkki (1995)
The chief goal of our research has been to clarify, if and how algebraic and statistical concepts could be used for the specification of statistical information systems (IS). Our research has resulted in a new algebraic framework of statistical ISs. The algebraic IS framework differs from other specification frameworks, because it introduces algebraic specifications of statistical ISs based on algebraic specifications of control systems (CS) and object systems (OS). The algebraic IS framework is an application of algebraic system theory. The algebraic specification of an IS comprises two functions, ie, an input function and an output function. The input function changes the information base of the IS on the basis of objects in the environment of the IS or within the IS and the output function derives information from the information base. The input function is composed of derivation and transition functions, and the output function is composed of derivation functions. The practical benefits of the algebraic IS framework can be productivity gains: better statistical applications and cost reductions in application production. The comprehensive algebraic IS framework also gives a theoretical structure, concepts and a universal language which could be used to describe and analyze statistical ISs.